1990
DOI: 10.1227/00006123-199006000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Paralysis Associated with Myelomeningocele: Clinical and Experimental Data Implicating a Preventable Spinal Cord Injury

Abstract: Paralysis seen in children with myelomeningocele has been attributed to congenital myelodysplasia. We suspected that paralysis may be due in part to a spinal cord injury caused by exposure of the neural tube to the amniotic fluid. This hypothesis was tested using a fetal rat model of surgically created dysraphism. Each pup from the experimental group of rats in which the spinal cord was intentionally exposed to the amniotic fluid was born with severe deformity and weakness of the hind limbs and tail. Control f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0
12

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(181 citation statements)
references
References 0 publications
4
165
0
12
Order By: Relevance
“…Authors of some previous studies have described inflammatory signs in the late gestational stages of MMC fetuses. 13,20 George and Cummings 10 have described significant inflammatory infiltrates in specimens obtained during surgical correction of MMC, and Hutchins et al 15 have reported that MMC placodes from stillborn infants have evidence of erosion, but Sival et al 27 have found only inflammatory tissue on the MMC surface in a 39-week-old newborn. These inflammatory findings in cases of MMCs in humans are difficult to interpret given that these inflammations can be caused by surgery or lesions occurring during delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors of some previous studies have described inflammatory signs in the late gestational stages of MMC fetuses. 13,20 George and Cummings 10 have described significant inflammatory infiltrates in specimens obtained during surgical correction of MMC, and Hutchins et al 15 have reported that MMC placodes from stillborn infants have evidence of erosion, but Sival et al 27 have found only inflammatory tissue on the MMC surface in a 39-week-old newborn. These inflammatory findings in cases of MMCs in humans are difficult to interpret given that these inflammations can be caused by surgery or lesions occurring during delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of several pathophysiological studies have challenged the concept that an intrinsic embryonic error is the sole determinant of an MMC lesion and instead have favored the hypothesis that the intrauterine environment is a major cause of injury to the placode, through either trauma or chemical toxicity. 5,9,13,15 Based on the concept that neurological deficits caused by the MMC lesion occur during the second half of gestation, in utero surgical correction of MMC in humans was initiated a decade ago. 4 The clinical outcomes of in utero surgery have suggested clear improvement in some neurological lesions, namely in the reversal of ectopic cerebellar tonsils of the MMC-associated Chiari malformation, decreasing it from 95 to 38%, with a consequent reduction in the need for a ventricular shunt from 91 to 59%.…”
mentioning
confidence: 99%
“…Similarly, the oncofetal antigen CA 19-9 may diffuse to the maternal circulation through the amniotic fluid in open NTDs. Previous experimental studies in animals showed that exposure of the spinal cord to amniotic fluid contributes to local tissue inflammation and associated neurological sequelae [12,13]. Neuronal inflammation can also lead to elevated serum CA 19-9 levels [14].…”
Section: Www Journalsviamedicapl/ginekologia_polskamentioning
confidence: 99%
“…Mechanical rub bing against the wall of the uterus and chemical toxicity from the amniotic liquid, especially after the 34th week, have been proposed as causes of neural damage. 5,9,12,14 As a consequence of this damage, after birth, patients with MMC suffer from paralysis (usually paraplegia), distal deformities, and bladder and bowel dysfunction.…”
Section: ©Aans 2013mentioning
confidence: 99%